Hexaaquacobalt(II) bis[4-(pyridin-2-ylmethoxy)benzoate] dihydrate - Zhang, Li-Wei (International Union of Crystallography, 2011)
The Co(II) atom in the title salt, [Co(H(2)O)(6)](C(13)H(10)NO(3))(2)·2H(2)O, lies on a center of inversion in an octahedron of water molecules. The cations, anions and uncoordinated water molecules are linked by O—H⋯O and O—H⋯N hydrogen bonds into a three-dimensional network. The anion is essentially planar, with an r.m.s. deviation of all non-H atoms of 0.066 Å.